Metal–Organic Frameworks‐Derived Mesoporous Si/SiOx@NC Nanospheres as a Long‐Lifespan Anode Material for Lithium‐Ion Batteries. Issue 51 (20th August 2019) - Majeed, Muhammad K.; Ma, Guangyao; Cao, Yanxiu; Mao, Hongzhi; Ma, Xiaojian; Ma, Wenzhe
Abstract: Silicon (Si)‐based anode materials with suitable engineered nanostructures generally have improved lithium storage capabilities, which provide great promise for the electrochemical performance in lithium‐ion batteries (LIBs). Herein, a metal–organic framework (MOF)‐derived unique core–shell Si/SiO x @NC structure has been synthesized by a facile magnesio‐thermic reduction, in which the Si and SiO x matrix were encapsulated by nitrogen (N)‐doped carbon. Importantly, the well‐designed nanostructure has enough space to accommodate the volume change during the lithiation/delithiation process. The conductive porous N‐doped carbon was optimized through direct carbonization and reduction of SiO2 into Si/SiO x simultaneously. Benefiting from the core–shell structure, the synthesized product exhibited enhanced electrochemical performance as an anode material in LIBs. Particularly, the Si/SiO x @NC‐650 anode showed the best reversible capacities up to 724 and 702 mAh g −1 even after 100 cycles. The excellent cycling stability of Si/SiO x @NC‐650 may be attributed to the core–shell structure as well as the synergistic effect between the Si/SiO x and MOF‐derived N‐doped carbon. Abstract : Mesoporous Si/SiO x @NC nanospheres : A core–shell structured Si/SiO x @NC composite with distinct nanostructure was controllably synthesized through metal–organic framework (MOF)‐derived magnesio‐thermic reduction. Owing to the core–shell structure, the final product with the optimized nanostructure exhibits enhanced electrochemical performance in terms of reversible capacity and long‐term cycling stability, which may be attributed to the many beneficial factors.